Pharmacokinetics and bioavailability of furosemide in sheep - Durna Corum, Duygu; Corum, Orhan; Atik, Orkun; Cetin, Gul; Zhunushova, Aidai; Uney, Kamil (Wiley, 2020)
AbstractThe pharmacokinetics and bioavailability of furosemide were determined following intravenous (IV), intramuscular (IM), and subcutaneous (SC) administrations at 2.5 mg/kg dose in sheep. The study was conducted on six healthy sheep in a three‐way, three‐period, crossover pharmacokinetic design with a 15‐day washout period. In first period, furosemide was randomly administered via IV to 2 sheep, IM to 2 sheep and SC to 2 sheep. In second and third periods, each sheep received furosemide via different routes of administration with the 15‐day washout period. Plasma concentrations were determined using a high‐performance liquid chromatography assay and analyzed by noncompartmental method. The mean total clearance and volume of distribution at steady state following IV administration were 0.24 L h‐1 kg‐1 and 0.17 L/kg, respectively. The elimination half‐life was similar for all administration routes. The mean peak plasma concentrations of IM and SC administration were 10.33 and 3.18 μg/ml at 0.33 and 0.42 hr, respectively. The mean bioavailability of IM and SC administration was 97.91% and 37.98%, respectively. The IM injection of furosemide may be the alternative routes in addition to IV. However, further research is required to determine the effect of dose and route of administration on the clinical efficacy of furosemide in sheep.
Keywords: Cross-Over Studies; Sheep; Furosemide; Area Under Curve; Injections, Intravenous; Animals; Biological Availability; Injections, Intramuscular; Half-Life